Situation analysis for delivering integrated comprehensive sexual and reproductive health services in humanitarian crisis condition for Rohingya refugees in Cox’s Bazar, Bangladesh: Protocol for a mixed-method study - Ahmed, Rushdia; Farnaz, Nadia; Aktar, Bachera; Hassan, Raafat; Shafique, Sharid Bin; Ray, Pushpita; Awal, Abdul; Rahman, Atiya; Urbaniak, Veronique; Kobeissi, Loulou Hassan; Rosie, Jeffries; Say, Lale; et al. (BMJ, 2022)
This article was published in the BMJ Open [© Author(s) (or their employer(s)) 2019. Re-use permitted under CC BY. Published by BMJ. This is an open access article distributed in accordance with the Creative Commons Attribution 4.0 Unported (CC BY 4.0) license] and the definite version is available at: http://dx.doi.org/10.1136/bmjopen-2018-028340 The Journal's website is at: https://bmjopen.bmj.com/content/9/7/e028340